There Is Worse: The Serpent’s Curse Compared to That of Eve. For a New Order - Ombrosi, Orietta (Religions, 2024)
By interpreting both the account of Creation found in Genesis 3 and the related exegetical interpretations of the text, this article aims to focus on the figure of the serpent, which has always been laden with a negative, even ruthless, symbolic meaning traditionally approached as almost entirely irrevocable. Taking ‘original nakedness’ as the key perspective, this brief study seeks to bring out and highlight the moment or condition preceding the curse, in which the serpent is revealed to be at once extremely similar to and radically different from humans, an animal as well but profoundly different from other animals: ill-placed. Sharing its solitude and alienation in this slippery and uncomfortable boundary position, participating in its desire, its temptation to encounter the other and to change places, to blur the boundaries of creation, this article listens to the serpent’s call to another story and follows it/him in an attempt to reimagine and rewrite another genesis, this time from its/his point of view, to displace and mix-up the established order and to find, in the end, a new dignity for itself/himself and for other animals.